'Byron's Fletcher' and 'Byron's Lega'. Issue 2 (December 2017) - Falloon, Anne
Abstract : Byron's two senior servants, William Fletcher and Antonio Lega Zambelli, were men from very different worlds and social classes, whose lives and those of their shared family were affected by the connection for decades after their deaths. Over the later nineteenth century, the Fletcher-Zambelli family sought respectability and began to rewrite their past. Rejecting links with Byron while elevating their own ancestry, a harmless obsession eventually turned into madness for one descendant. This essay unearths previously unpublished manuscripts and photographs from collections held privately and in the Devon Archives.